Combined X-linked familial exudative vitreoretinopathy and retinopathy of prematurity phenotype in an infant with mosaic turner syndrome with ring X chromosome. (4th March 2023) - Hoyek, Sandra; Wang, Marlene; Berrocal, Audina M.; Wong, Ashley; Place, Emily M.; Mason-Suares, Heather; Lin, Angela E.; Mukai, Shizuo; Patel, Nimesh A.
ABSTRACT: Background: Retinopathy of prematurity (ROP) and familial exudative vitreoretinopathy (FEVR) are two distinct pathologies of retinal angiogenesis with overlapping clinical features. Methods: Examination, multimodal imaging, and genetic testing were used to guide diagnosis and treatment. Results: We report a combined phenotype of X-linked FEVR and ROP in a 4-month-old girl with mosaic Turner syndrome with ring X chromosome born at 26 weeks gestational age. She was initially diagnosed with atypical ROP with a vitreous band causing a localized traction retinal detachment, inferotemporal to the macula in the right eye, vessels to posterior zone 2 with no clear ridge temporally in the left eye, and fluorescein leakage in both eyes. Due to the suspicion of concurrent FEVR, genetic testing using a vitreoretinopathy panel was performed which revealed a mosaic Turner syndrome associated with 45, X/46, X, r(X), subsequently confirmed by chromosome analysis. The deleted region in the ring X chromosome included the NDP and RS1 genes. The patient was treated with laser photocoagulation of the peripheral avascular retina and sub-Tenon's triamcinolone injection in both eyes, intravitreal injection of bevacizumab in the left eye, and pars plicata vitrectomy in the right eye. Conclusions: In premature neonates with atypical ROP, a clinical suspicion of concurrent FEVR or similar vasculopathy is important and genetic testing may elucidate a genetic etiology, which could influence management and prognosis. Turner syndrome can be connected with co-occurring Mendelian gene disorders, particularly in individuals with mosaicism. The concurrence of FEVR and ROP appears to result in atypical and possibly more severe phenotypes.